#### Answer

x = 5, -3

#### Work Step by Step

(x-4)(x+2) = 7
$x^2-2x-8 = 7$
$x^2-2x-15=0$
$(x-5)(x+3)=0$
x = 5 or -3

Chegg costs money, GradeSaver solutions are free!

Published by
Cengage Learning

ISBN 10:
9781337271172

ISBN 13:
978-1-33727-117-2

x = 5, -3

(x-4)(x+2) = 7
$x^2-2x-8 = 7$
$x^2-2x-15=0$
$(x-5)(x+3)=0$
x = 5 or -3

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.